Comparison between millennials' and providers' perceptions of technology use in a nature-based tourism context. Issue 13 (3rd July 2022) - Clark, Connor; Nyaupane, Gyan P.; Lichterman, Andrea
ABSTRACT: This mixed-methods study examined millennials' and nature-based tourism providers' perceptions of the use of technology in a nature-based tourism context. The data were collected through surveys and focus groups of millennials and nature-based tourism providers. Survey findings revealed that millennials perceived a number of technologies more negatively than providers, challenging common stereotypes. Focus group responses further demonstrated providers' assumptions regarding millennials' dependence on technology as well as millennials' conflicting needs to escape from ordinary technology use during nature-based tourism activities while remaining connected to essential technology services. The implications of catering to millennials' nature-based tourism needs are discussed.